Assessment of Practical and Scientific Writing Skills for Pre-University Students through Project-Based Learning - Wan Roslina, Wan Yusof; Melody, Kimi; Wan Sharifatun Handayani, Wan Zullkiplee; Mohd Alhafiizh, Zailani; Mardhiah, Shahabudin; Abdul Al-Hafiz, Ismail; Sharifah Mona, Abd. Aziz Abdullah; Iswan Nur Ariff, Ismail; Dhana Jay, Raja Gopal (American Chemical Society, 2021)
Chemistry is one of the STEM (science, technology, engineering, and mathematics) subjects that has been perceived as an unattractive subject among students due to its scientific theories and practices in a laboratory. Practical and scientific writing skills are two crucial components in chemistry courses, including at the Pre-University level, thus requiring educators to design activities that integrate both skills in chemistry learning. This article describes the assessment using a projectbased learning approach to assess students’ practical and scientific writing skills for the Organic Chemistry course at the Universiti Malaysia Sarawak Foundation in Science program. A total of 72 PreUniversity science students participated in a Chemistry Group Project assessment. The students were divided into 6 groups and asked to write a proposal on the basis of a chosen title, conduct laboratory work, collect data, and prepare a final report. The assessment was conducted in a single semester from learning week 1 to learning week 17. Results of this study were collected through the submitted proposal, final reports, practical sessions, and students’ feedback. Students obtained good marks for practical and scientific writing with average marks of 84.9% and 84.4%, respectively. The results revealed that implementing the Chemistry Group Project as project-based learning leads to increased performance in practical and scientific writing skills and social skills among Pre-University students. Therefore, the Chemistry Group Project should be conducted as one of the learning activities and practical approaches at the Pre-University level.